Role of Initial Preoperative Medical Management in Controlling Post-Operative Anterior Uveitis in Patients of Phacomorphic Glaucoma - A. Rehman, Mumtaz Hussain, Irfan Qayyum Malik, M. Moin (Pakistan Journal of Ophthalmology, 2011)
Purpose: To determine the role of initial preoperative medical treatment in controlling severe post operative anterior uveitis after cataract surgery in patients of phacomorphic glaucoma. Material and Method: After diagnosis of phacomorphic glaucoma patients were divided into two groups. Group A included 30 eyes which were operated very next day after controlling intraocular pressure only. Group B included 30 eyes which were given anti-glaucoma andfour hourlytopical steroid drops to reduce inflammation for at least 5 days and then they were operated. Patients in both the groups were operated by extra capsular cataract extraction technique with intra ocular lens implantation by a single surgeon. Evaluation of patients on slitlamp for the signs of postoperative inflammation in both the groups was done on the first three post operative days while the patients were in the ward. Follow up visits were done after one week, three weeks and finally after six weeks postoperatively. Results: The study was conducted on 60 eyes at eye department, Mayo hospital Lahore. On first postoperative day Group A slitlamp findings showed, +2 cells in 3eyes, 27 eyes showed >+3 cells,27 eyes showed corneal edema, 12 eyes showed membrane in A/C, and 7 eyes showed hypopyon. While in Group B slitlamp findings showed, +1 cells in 7 eyes, +2 cells in 20eyes, 3 eyes showed >+3 cells,2 eyes showed corneal edema, 2 eyes showed membrane in A/C, and no eye showed hypopyon. The data was analyzed statistically by applying T test using SPSS version 8. Conclusion: Preoperative reduction of inflammation in phacomorphic glaucoma helps to minimize post operative complications due to anterior uveitis.